2021
DOI: 10.3390/biomechanics1010009
|View full text |Cite
|
Sign up to set email alerts
|

Margin of Stability May Be Larger and Less Variable during Treadmill Walking Versus Overground

Abstract: Margin of stability (MOS) is considered a measure of mechanical gait stability. Due to broad application of treadmills in gait assessment experiments, we aimed to determine if walking on a treadmill vs. overground would affect MOS during three speed-matched conditions. Eight healthy young participants walked on a treadmill and overground at Slow, Preferred, and Fast speed-matched conditions. The mean and variability (standard deviation) of the MOS in anterior-posterior and mediolateral directions at heel conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…However, during this process of sensory reweighting from unreliable to reliable sensory system, the increase/decrease of MOS could be observed to maintain dynamic gait stability (McAndrew et al, 2011 ). Based on the formula of MOS (Süptitz et al, 2012 ; Fallahtafti et al, 2021 ), two factors could lead to a larger MOS: (1) the BOS was toward COM or (2) XCoM was far away from COM. In the current study, the spatial gait parameter supported that a larger MOSap was attributed to the BOS being toward the COM (shorter step length) when both types of mastoid vibrations were applied compared to the condition of no vibration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, during this process of sensory reweighting from unreliable to reliable sensory system, the increase/decrease of MOS could be observed to maintain dynamic gait stability (McAndrew et al, 2011 ). Based on the formula of MOS (Süptitz et al, 2012 ; Fallahtafti et al, 2021 ), two factors could lead to a larger MOS: (1) the BOS was toward COM or (2) XCoM was far away from COM. In the current study, the spatial gait parameter supported that a larger MOSap was attributed to the BOS being toward the COM (shorter step length) when both types of mastoid vibrations were applied compared to the condition of no vibration.…”
Section: Discussionmentioning
confidence: 99%
“…A more negative MOSap was observed as the walking speed increased. In other words, a more negative MOSap indicated that the margin was exceeded, and the extrapolated COMap was outside of the BOS (Fallahtafti et al, 2021 ). In the current study, we defined that a more negative MOSap indicated a larger MOSap.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations